(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
In this paper, we introduce a new type of semigroup, namely (Quotient semigroup) in differential equations with the functional analytic. This semigroup constructs the solution of the partial differential equations as the form: